THE EFFECT OF INVESTMENT OPPORTUNITY SET, INSTITUTIONAL OWNERSHIP, AND COMPANY SIZE ON THE QUALITY OF EARNINGS ON COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (PERIOD 2018-2020) - Imam Hidayat; Rika Dwi Utami (AJAR, 2022)
This study aims to determine the effect of investment opportunity set, institutional ownership, and company size on earning quality. Of the 52 companies in the consumption sector, there are 22 sample companies and will be analyzed from 2018 to 2020. This type of research uses a quantitative approach with the panel data regression method, which is processed with EViews version 12. The result shows that investment opportunity set and institutional ownership has no positive and significant effect on earnings quality. Firm size has a positive effect and significant effect on earnings quality.